#
If p(x) = x 2 + 3, then find p(2) + p(-2)

pls tell me the

ans fast

## Answers

Answered by

0

**Answer:**

The value of p(-2) = 11

Step-by-step explanation:

We have,

p(x)=x^2-2x+3p(x)=x

2

−2x+3

To find, the value of p(-2) = ?

∴ p(x)=x^2-2x+3p(x)=x

2

−2x+3

Put p = - 2, we get

p(-2)=(-2)^2-2(-2)+3p(−2)=(−2)

2

−2(−2)+3

⇒ p(-2) = (- 2)^2 - 2( - 2) + 3

⇒ p(-2) = 4 + 4 + 3

⇒ p(-2) = 11

∴ The value of p(-2) = 11

Thus, the value of p(-2) is equal to 11

**Step-by-step explanation:**

this is ur answer hope it helps u

Answered by

0

**Answer:**

**Step-by-step explanation:**

☞we have,

p(x)=x²-2x+3

☞ To find, the value of p(-2) = ?

∴ p(x)=x²-2x+3

☞Put p = - 2, we get

p(-2)=(-2)²-2(-2)+3

p(−2)=(−2) ² −2(−2)+3

⇒ p(-2) = (- 2)² - 2( - 2) + 3

⇒ p(-2) = 4 + 4 + 3

⇒ p(-2) = 11

∴ The value of p(-2) = 11

☞Thus, the value of p(-2) is equal to 11.

Hope it's helpful↑(◍•ᴗ•◍)❤࿐

✶⊶⊷⊶⊷❍ ❥ ❍⊶⊷⊶⊷✶

Similar questions